Deadly censorship : murder, honor, & freedom of the press - Underwood, James L. (University of South Carolina Press, 2013)
On January 15, 1903, South Carolina lieutenant governor James H. Tillman shot and killed Narciso G. Gonzales, editor of South Carolina's most powerful newspaper, the State. Blaming Gonzales's stinging editorials for his loss of the 1902 gubernatorial race, Tillman shot Gonzales to avenge the defeat and redeem his "honor" and his reputation as a man who took action in the face of an insult. Here, the author investigates the epic murder trial of Tillman to test whether biting editorials were a legitimate exercise of freedom of the press or an abuse that justified killing when camouflaged as self-defense. This clash - between the revered values of respect for human life and freedom of expression on the one hand and deeply ingrained ideas about honor on the other - took place amid legal maneuvering and political posturing worthy of a major motion picture. One of the most innovative elements of this book is the author's examination of homicide as a deterrent to public censure. He asks the question, "Can a man get away with murdering a political opponent?" This is a courtroom drama and a true story. The author offers a painstaking re-creation of an act of violence in front of the State House, the subsequent trial, and Tillman's acquittal, which sent shock waves across the United States. A specialist on constitutional law, the author has written a definitive examination of the court proceedings, the state's complicated homicide laws, and the violent cult of personal honor that had undergirded South Carolina society since the colonial era.